Interaction of Uric Acid and Neutrophil-to-Lymphocyte Ratio for Cardiometabolic Risk Stratification and Prognosis in Coronary Artery Disease Patients - Serena Del Turco; Luca Bastiani; Fabrizio Minichilli; Patrizia Landi; Giuseppina Basta; Alessandro Pingitore; Cristina Vassalle (MDPI AG, 2022)
Oxidative stress and inflammation are key factors in cardiometabolic diseases. We set out to evaluate the relationship between serum uric acid (UA) and the neutrophil-to-lymphocyte ratio (NLR) with cardiometabolic risk factors in coronary artery disease (CAD) patients, and their additive and multiplicative interactive effects on outcomes (cardiac death/CD and hard events (HE)-death plus reinfarction). A total of 2712 patients (67 ± 11 years, 1960 males) who underwent coronary angiography was retrospectively analyzed and categorized into no-CAD patients (n = 806), stable-CAD patients (n = 1545), and patients with acute myocardial infarction (AMI) (n = 361). UA and NLR were reciprocally correlated and associated with cardiometabolic risk factors. During a mean follow-up period of 27 ± 20 months, 99 ± 3.6% deaths, and 213 ± 7.8% HE were registered. The Kaplan-Meier survival estimates showed significantly worse outcomes in patients with elevated UA or NLR levels. Multivariate Cox regression analysis demonstrated that NLR independently predicted CD and HE. There was no multiplicative interaction between UA and NLR; however, the use of measures of additive interaction evidenced a positive additive interaction between UA and NLR for CD and HE. Although it is clear that correlation does not imply causation, the coexistence of NRL and UA appears to have a synergistic effect, providing further information for the risk stratification of CAD patients.